Cell Death Is Counteracted by Mitophagy in HIV-Productively Infected Astrocytes but Is Promoted by Inflammasome Activation Among Non-productively Infected Cells - Ojeda, Diego S.; Grasso, Daniel; Urquiza, Javier; Till, Andreas; Vaccaro, María Inés; Quarleri, Jorge (Frontiers in Immunology, 2018)
Despite more than 30 years of extensive research efforts, a complete understanding of the neurological consequences of HIV central nervous system (CNS) infection remains elusive. HIV is not only able to establish a viral reservoir in the CNS but also to initiate manifestation of neurodegenerative diseases. These neurological disorders may arise because of virus-induced activation of the inflammasome in CNS cells, including astrocytes. Nevertheless, in some productive viral infection scenarios, selective autophagy may reduce inflammation through mitochondrial degradation (‘mitophagy’) to counteract inflammasome activation. In this study, using cultured human astrocytes, we demonstrate that - depending on the HIV infection outcome - cells may resist death, or succumb by inflammasome activation when viral infection is productive or abortive, respectively. Cells productively infected with HIV were able to attenuate both mitochondrial ROS production and mitochondrial membrane potential dissipation, thus exhibiting cell death resistance. Interestingly, mitochondrial injury was counteracted by increasing the autophagic flux and by activating mitophagy. Conversely, astrocytes exposed to HIV in an abortive scenario showed prominent mitochondrial damage, inflammasome activation, and cell death. This bystander effect occurred after cell-to-cell contact with HIV-productively infected astrocytes. In summary, we demonstrate a tight functional crosstalk between viral infection mode, inflammasome activation, autophagy pathways and cell fate in the context of HIV infection. Moreover, mitophagy is crucial for cell death resistance in HIV-productively infected astrocytes, but its impairment may favor inflammasome-mediated cell death in abortively infected cells.